The Maryland Aggregate Pathology Index: A Deceased Donor Kidney Biopsy Scoring System for Predicting Graft Failure - Munivenkatappa, R. B.; Schweitzer, E. J.; Papadimitriou, J. C.; Drachenberg, C. B.; Thom, K. A.; Perencevich, E. N.; Haririan, A.; Rasetto, F.; Cooper, M.; Campos, L.; Barth, R. N.; Bartlett, S. T.; et al. (American journal of transplantation, 2008)
Despite the common use of diagnostic pretransplant deceased donor kidney biopsy, there is no consensus on the prognostic significance of the pathologic findings. In order to assist clinicians with interpretation we analyzed 371 pretransplant biopsies and correlated the findings with graft failure. Glomerular pathology was assessed with percent glomerulosclerosis (GS), glomerular size and periglomerular fibrosis (PGF); vascular pathology with arterial wall‐to‐lumen ratio (WLR) and arteriolar hyalinosis and interstitial pathology with measurement of cumulative fibrosis and presence of scar. Using two‐thirds of the study population as a model‐development cohort, we found that biopsy features independently associated with an increased risk of graft failure were GS ≥15%, interlobular arterial WLR ≥0.5 and the presence of PGF, arteriolar hyalinosis or scar. The Maryland Aggregate Pathology Index (MAPI), was developed from these parameters and validated on the remaining one‐third of the population. Five‐year actuarial graft survival was 90% for kidneys with MAPI scores between 0 and 7, 63% for scores from 8 to 11 and 53% for scores from 12 to 15 (p < 0.001). We conclude MAPI may help transplant physicians estimate graft survival from the preimplantation biopsy findings, in clinical situations similar to this study population (cold ischemia over 24 h, GS < 25%). A composite histopathology score developed on pre‐transplant biopsies of deceased donor kidneys, based on glomerulosclerosis, fibrosis, arterial wall thickening, and other features correlated strongly with graft survival at five years. See editorial by Mengel in this issue on page 2181.